2023
DOI: 10.1039/d3sc01699d
|View full text |Cite
|
Sign up to set email alerts
|

A sustainable, efficient, and potentially cost-effective approach to the antimalarial drug candidate MMV688533

Abstract: A 6-step synthesis of the antimalarial drug candidate MMV688533 is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Overall, the synthesis of MMV688533 presented by Kavthe et al 10 demonstrates how environmentally orientated methods can translate to more sustainable synthesis. By developing a new synthetic route featuring Sonogashira couplings under aqueous micellar conditions: PMI, catalyst loading, step economy and yield could all be simultaneously improved.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Overall, the synthesis of MMV688533 presented by Kavthe et al 10 demonstrates how environmentally orientated methods can translate to more sustainable synthesis. By developing a new synthetic route featuring Sonogashira couplings under aqueous micellar conditions: PMI, catalyst loading, step economy and yield could all be simultaneously improved.…”
mentioning
confidence: 98%
“…Quantitatively assessing the production of waste in both syntheses found that the process mass intensity (PMI) of the newly reported route (111 kg input per kg product) is less than half of what was calculated for the discovery route (287 kg input per kg product), highlighting the level of improvement in sustainability that this work has achieved. 14 Overall, the synthesis of MMV688533 presented by Kavthe et al 10 demonstrates how environmentally orientated methods can translate to more sustainable synthesis. By developing a new synthetic route featuring Sonogashira couplings under aqueous micellar conditions: PMI, catalyst loading, step economy and yield could all be simultaneously improved.…”
mentioning
confidence: 99%
See 1 more Smart Citation